Effectiveness and safety of tegafur-gimeracil-oteracil potassium (TS-1) for metastatic breast cancer: a single-center retrospective study - Ishizuna, Kazuo; Ninomiya, Jun; Ogawa, Toshihisa; Kojima, Makoto; Tsuji, Eiichi; Kawashima, Miho; Nozaki, Miwako; Yamagishi, Hidetsugu; Ueda, Yoshihiko (Gan to kagaku ryoho, 2014)
Tegafur-gimeracil-oteracil potassium (TS-1)is a drug that is used mainly as a third-line treatment or beyond for metastatic breast cancer(MBC). However, there is still insufficient evidence on its clinical effectiveness, and there are very few reports on clinical research using TS-1 up front. In this report, we examined the effectiveness and safety of TS-1 therapy for MBC. The subjects were 46 patients with MBC who were treated with TS-1 between January 2005 and January 2013. These patients were retrospectively examined. The objective response rate to TS-1 therapy was 30.4%, clinical benefit rate (CBR)was 50.0%, and the median time to treatment failure was 10.7 months. When examined by site, the CBR was high locally (46.2%), in the lymph nodes (40.7%), in the bone (42.9%), and in the lungs and pleura (44.8%). However it was low in the liver(30.0%). The relationship was examined between clinicopathological factors and the effectiveness of TS-1 therapy. The objective response rate (ORR) was significantly higher for patients with disease-free interval (DFI) of 2 years or more (p=0.039), TS-1 therapy used as third-line treatment or earlier (p=0.022), negative HER2 status (p=0.020), and no history of capecitabine (CAP)therapy (p=0.049). The CBR was significantly higher for patients with no visceral metastasis (p=0.032), TS-1 used as third-line treatment or earlier (p=0.019), negative HER2 status (p= 0.045), no history of CAP therapy (p=0.006), and no history of tegafur-uracil/doxifluridine therapy (p=0.031). Multivariate analysis showed that DFI of 2 years or more (p=0.035, odds ratio:0.104)was an independent predictor of effectiveness assessed by ORR. There were only 4 patients in whom the treatment was discontinued due to adverse event, and TS-1 was generally well tolerated. TS-1 was highly effective and well tolerated by patients with MBC. Its up-front use might enable the maintenance of satisfactory QOL and the enhancement of its clinical effectiveness.